IJAR 2020
DOI: 10.36106/ijar/6311464
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus Salivarius: An Unusual Etiology of Neonatal Sepsis

Abstract: Streptococcus salivarius is a rare cause of infection in neonate .It is a commensal organism in the oral cavity. Though commensal it can cause invasive infection in immune compromised patients. We report blood stream infection with streptococcus salivarius in a neonate with pneumonia. The blood stream infection was considered significant and treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Recently, Keerthi et al 9 reported an unusual presentation of neonatal pneumonia, presumptively due to S. salivarius at the chronological age of 44 days in an ex‐preterm infant of 35 weeks, presenting with fever and wheezing at the emergency department. However, we could not rule out the possibility of “contaminant” as it was identified in only a single hemoculture.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Keerthi et al 9 reported an unusual presentation of neonatal pneumonia, presumptively due to S. salivarius at the chronological age of 44 days in an ex‐preterm infant of 35 weeks, presenting with fever and wheezing at the emergency department. However, we could not rule out the possibility of “contaminant” as it was identified in only a single hemoculture.…”
Section: Discussionmentioning
confidence: 99%